Social support terhadap work-life balance pada karyawan - Mahda Nurhabiba (Fakultas Psikologi, 2020)
Work-life balance is a method that uses to help an employees reduce the conflict which unbalanced dual role. An individual needs to balance between his personal life and his work. Work-life balance in an employee is very important, while social support can be something that can encourage employees to carry out their obligations. This study aim to determined the effect of social support on work-life balance on employees. Research subjects 100 employees at PT. PLN PERSERO using quota sampling technique. Data collection used a scale of social support and work-life balance, data analysis used simple linear regression. Sig value Regression of 0.000 <0.05 shows the result that there is a significant influence between social support and work-life balance on employees. Social support contributes 24.5% to work-life balance. The results of this study provide evidence that a hypothesis stating that there is an influence between social support towards work-life balance is accepted. So with the proven hypothesis explaining that social support is one of the work-life balance factors.